2023
DOI: 10.4103/idoj.idoj_284_22
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculids: A narrative review

Abstract: Tuberculids are a group of dermatoses with tuberculoid histology and the absence of tubercle bacilli. They are considered to be hypersensitivity reactions to circulating Mycobacterium tuberculosis (M. tb) or its antigens in individuals with good immunity. The objective of the review is to provide a detailed literature review of all available articles on tuberculids in the past 10 years and provide an update on epidemiology, etiopathogenetic mechanisms, clinical manifestations, and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
2
3
0
Order By: Relevance
“…Diagnosis is aided by strong Mantoux positives, distinctive histological characteristics, and the lack of M. tuberculosis in culture. Treatment is conservative with antituberculous drugs as used for systemic tuberculosis [5,6]. All these were noted in the present case.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Diagnosis is aided by strong Mantoux positives, distinctive histological characteristics, and the lack of M. tuberculosis in culture. Treatment is conservative with antituberculous drugs as used for systemic tuberculosis [5,6]. All these were noted in the present case.…”
Section: Discussionsupporting
confidence: 56%
“…A study of 221 patients revealed that 70.5% of them were children. The trunk was the primary area affected (98.6%), followed by the lower limb (25.33%), upper limb (15.83%), face (5%), and external genitalia (3.6%) [5,9]. In the present case, the trunk was also mainly involved.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…For example, tuberculids, a paucibacillary form of cutaneous TB, develop as immunological reactions to antigenic components of mycobacteria and usually occur in patients with a good cellular immunity. 13 Conversely, in our patient who was severely immunocompromised, the lesions were multibacillary, as evidenced by the positive stain for acid-fast bacilli on the pus aspirated.…”
Section: Discussionmentioning
confidence: 55%